A Negociação de Sinais em Libras como Possibilidade de Ensino e de Aprendizagem de Geometria - De Sales, Elielson Ribeiro [UNESP]; Penteado, Miriam Godoy [UNESP]; Moura, Amanda Queiroz [UNESP] (FapUNIFESP (SciELO), 2015)
The theme on the inclusion of people with special educational needs is increasingly present in the academic and school environment. This article discusses a process of negotiation of signs in Brazilian sign language, Libras, carried out with deaf students in the early years of a public elementary school. Among the different relevant aspects in this teaching activity within the classroom, the interaction concerning geometry as a central theme is highlighted. The first section of the article presents aspects related to deafness and to the education of deaf people. In the following are presented the contexts of activity as well as excerpts of conversations in which students make agreement on the signs for different geometric figures, which were absent in the dictionaries. The results indicate the importance of the negotiation process for the enlargement of the lexical field in Libras, as well as for the engagement of students in the activity, as this process offers an opportunity to explore mathematical properties. Finally, it is acknowledged that the inclusion of disabled students in the regular school seems to be well supported by legislation concerning the access, although more efforts are still needed in order to ensure learning spaces for everybody.
The negotiation of signs in Brazilian sign language as a possibility for the teaching and learning of geometry
Keywords: Brazilian Sign Language; Geometry; Inclusive Education; Mathematics Education and Deafness; Teaching and Learning of Mathematics